Pembelajaran konsep asidimetri dan stoikiometri menggunakan chemcollective’s virtual chemistry laboratory - Rizki Dwi Ningsih; Evelin Natasyah; Sony Ananta; Prima Fitra; Naila Rahmi; Riryn Novianty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Chemistry cannot be separated from laboratory experiments as a form of increasing understanding and proof of the chemical theory. The problem is that chemical practices require a very large budget and high handling facilities, equipment facilities, chemicals and storage facilities. So there is a new learning method that uses Chemcollective's Virtual Chemistry Laboratory Technology Application by simulating a chemical lab in a computer application called Virtual Lab / Vlab. This is intended to facilitate the understanding of chemistry through practical simulation and solving solutions for the limitations of laboratory equipment. The method used is the stage of software installation and training to practice the chemicals with Vlab. Learning practicum objects with Vlab is one of them is Acidimetry and Stoichiometry. Stoichiometry is chemistry that studies quantitative relationships between substances involved in chemical reactions. Acidimetric titration is the process of determining the concentration of bases using acid solutions as a standard. On Acidimetri Pre Test 54 and Post Test 70, object Stoichiometry Pre Test 80 and Post Test 81. The significant results of the Post Test versus Pre Test in training at SMAN 1 BungarayaSiak have shown that the Vlab method can improve students' understanding of the concept of chemistry. and it was concluded that the Vlab was very good for further introduction, study and application at different schools.